Pigmentation of a Camouflage Dye and Investigation of Its Colour and Reflectance Properties - BALBASI*, MUZAFFER; ARDAHANLIOGLU, YAVUZ (Asian Journal of Chemistry, 2024)
Natural foliage and terrain reflect light both in the visible (380-700 nm) and near infrared (700-900 nm) regions of the electromagnetic spectrum. In this study, dyes consisting of several different pigment combinations are proposed intended to meet the camouflage needs fitting the reflectance properties of local natural green foliage in both visible and near infrared regions. Camouflage pigment green 179, functionalized with the appropriate infrared reflectance was mixed with varying amounts of chromium oxide, iron oxide and carbozel violet pigments and the spectral reflectance of surfaces treated with this alkide based dye was measured in the 320-1500 nm interval. Chromaticity and observed brightness (Y) values were determined using the CIELAB 1976 (L* a* b*) colour definition systems. Field tests demonstrate that dyes thus obtained, meet camouflage standards in both the visible and near infrared regions.